Meningkatkan Kemampuan Guru Dalam Memanfaatkan Lingkungan Sekolah Sebagai Sumber Belajar Melalui Pembelajaran PAIKEM GEMBROT Di KKG Guru SD Negeri 024763 Binjai Tahun Pelajaram 2016/2017 - Lisprija Lisprija (Universitas Islam Sumatera Utara, 2021)
One of the learning strategies accordance with the curriculum is learning with the PAIKEM GEMBROT approach, namely active, innovative, creative, effective, fun, happy and meaningful learning. By utilizing the school environment as a learning resource, the implementation of GEMBROT PAIKEM learning will enable students to develop their creativity, motivation and participation in learning. Meanwhile the reality is that many teachers who rarely or never even take advantage of the school environment as a learning resource. Likewise in KKG, the teacher's ability to discuss is still not active and creative, so that the teacher's ability to use the school environment as a learning resource is not good. This study was designed in the form of School Action Research that consisted of two cycles, where each cycle was carried out in two to three meetings. The subjects of this study were teachers at SD Negeri 024763 Binjai consisting of ten teachers. From the results of the implementation of the research, the following data were obtained: In the first cycle the average value obtained from the teacher's discussion attitude was 79.38 or